2007
DOI: 10.1038/nmeth1079
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA sponges: competitive inhibitors of small RNAs in mammalian cells

Abstract: MicroRNAs are predicted to regulate thousands of mammalian genes, but relatively few targets have been experimentally validated and few microRNA loss-of-function phenotypes have been assigned. As an alternative to chemically modified antisense oligonucleotides, we developed microRNA inhibitors that can be expressed in cells, as RNAs produced from transgenes. Termed 'microRNA sponges', these competitive inhibitors are transcripts expressed from strong promoters, containing multiple, tandem binding sites to a mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

36
1,579
0
4

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,915 publications
(1,619 citation statements)
references
References 21 publications
36
1,579
0
4
Order By: Relevance
“…Conversely, vectors expressing 'microRNA sponges' could be used to inhibit miRNA sequences. 18 In a similar manner, vectors expressing short hairpin RNA could be administered to the fetal brain to knockdown a gene's expression and evaluate its function in development. This would have particular relevance if the subsequent phenotype provided a useful model for neurodegenerative disease, circumventing the need for producing complex transgenic models.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, vectors expressing 'microRNA sponges' could be used to inhibit miRNA sequences. 18 In a similar manner, vectors expressing short hairpin RNA could be administered to the fetal brain to knockdown a gene's expression and evaluate its function in development. This would have particular relevance if the subsequent phenotype provided a useful model for neurodegenerative disease, circumventing the need for producing complex transgenic models.…”
Section: Discussionmentioning
confidence: 99%
“…To further address whether endogenous miR-764-5p acts as an attenuator for the CHIP expression, we designed an antagomiR sequence against miR-764-5p (named as miR-sponge) (19) and stably expressed the sequence using pcDNA3.1 vector in MC3T3-E1 cells. The result showed that the protein level of CHIP was increased when miR-sponge was stably expressed (Fig.…”
Section: Expression Of Mir-764-5p Is Upregulated During Oosteoblast Dmentioning
confidence: 99%
“…In an alternative strategy to single anti-miRs, Ebert et al (2007) recently developed miRNA inhibitors called 'miRNA sponges', which can be transiently expressed in cultured cells. These molecules are transcripts expressed from strong promoters, containing multiple tandem binding sites to specific miRNAs, and competitively inhibit them.…”
Section: Mirnas As Therapeuticsmentioning
confidence: 99%